Effect of Copper Foam Baffles on Thermal Hydraulic Performance for Staggered Arrangement in a Duct - karrar Fadhala; Ekhlas Fayyadh; Ali Mohammed (Engineering and Technology Journal, 2023)
Metal foam is a novel material recently utilized in baffles as an alternative to solid baffles for reducing flow resistance. However, copper foam baffles have been suggested in this research to overcome this issue. So, the experimental tests were carried out in a manufactured square channel (250 mm x 250 mm) and heated uniformly at the bottom wall of the test section.Its walls are mounted copper foam baffles at a fixed porosity of 95%.Baffles were fixed alternatively on the top and bottom of the walls in staggered mode between two successive baffles (center to center) and were kept constant at 250 mm. The experimental work was done for different grades of the pore density of copper foam (10, 15, and 20 pores per inch (PPI)) with a window cut ratio of 25% and a constant heat flux of 4.4 kW/m2.Reynolds number was varied from 3.8x104 to 5.4x104. The data for conventional copper solid baffles were used to compare the effect of foam metal baffles.The obtained results manifested that relative to the solid-copper baffles, the copper foam baffles have a greatly lower friction factor, whereas the friction factor for the solid baffles and copper foam baffles (10, 15, and 20) PPI is about (460), and (20, 29, and 38) times, respectively above the smooth surface. Moreover, the results of previous work predicted the present experimental work very well.